Foreign accent syndrome post tonsillectomy: A case report. Issue 6 (2nd June 2022) - Corbett, Mel; O'Shea, John; Van Den Berg, Nadia; Lang, John
Abstract: Foreign Accent Syndrome (FAS) is a rare clinical entity in which affected patients experience a new pattern of speech resembling an unusual accent. Reported cases are scarce in published literature and are usually the result of a neurological insult. FAS as a complication from a general anesthetic or surgery has not been reported to date. We present the case of a healthy 27‐year‐old Australian woman who developed FAS following a tonsillectomy. Post operatively, speech patterns resembled an Irish accent. We discuss the potential mechanisms of the unusual complication as well as review the available literature surrounding FAS. Abstract : Foreign accent syndrome (FAS), is a rare clinical entity, which has not been reported in literature to date as a post‐operative complication. We discuss the potential mechanisms of this unusual complication.